SĄDOWNICTWO KONSTYTUCYJNE A AUTONOMIA PRAWA WOBEC POLITYKI - Smolak, Marek (Wydział Prawa i Administracji UAM, 2003)
The paper argues that the impact of the constitutional review on the autonomy of law before politics are closely connected with the way judges understand the rule of law, especially the rules of division of power and the rules of judges being bound by statute. The way judges understand the rule o f law, including the rules of division of power, is a political act, since judges’ decisions, just like other political decisions, can encounter choices between various options that are good but none of which is better than the others. The degree of extensiveness of this autonomy of law before politics depends on the accepted concept of rule o f law. The paper also affirms the role of rational practical discourse as a procedure of testing evaluative statements by the way of an argument for quaranteeing the autonomy of law before politics by the constitutional review.
THE CONSTITUTIONAL REVIEW AND THE AUTONOMY OF LAW BEFORE POLITICS